Association Analysis of Variants of DSCAM and BACE2 With Hirschsprung Disease Susceptibility in Han Chinese and Functional Evaluation in Zebrafish - Lu, Yan-Jiao; Yu, Wen-Wen; Cui, Meng-Meng; Yu, Xian-Xian; Song, Huan-Lei; Bai, Mei-Rong; Wu, Wen-Jie; Gu, Bei-Lin; Wang, Jun; Cai, Wei; Chu, Xun (Frontiers in Cell and Developmental Biology, 2021)
Hirschsprung disease (HSCR) has a higher incidence in children with Down syndrome (DS), which makes trisomy 21 as a predisposing factor to HSCR. DSCAM and BACE2 are close together on the HSCR-associated critical region of chromosome 21. Common variants of DSCAM and rare variants of BACE2 were implicated association with sporadic HSCR. However, the submucosal neuron defect of DS mouse model could not be rescued by normalizing of Dscam. We aimed to explore the contribution of DSCAM and BACE2 to the development of the enteral nervous system (ENS) and HSCR susceptibility. We genotyped 133 tag SNPs in DSCAM and BACE2 gene region in 420 HSCR patients and 1,665 controls of Han Chinese. Expression of DSCAM and BACE2 homologs was investigated in the developing gut of zebrafish. Overexpression and knockdown of the homologs were performed in zebrafish to investigate their roles in the development of ENS. Two DSCAM SNPs, rs430255 (PAddtive = 0.0052, OR = 1.36, 95% CI: 1.10-1.68) and rs2837756 (PAddtive = 0.0091, OR = 1.23, 95% CI: 1.05-1.43), showed suggestive association with HSCR risk. Common variants in BACE2 were not associated with HSCR risk. We observed dscama, dscamb and bace2 expression in the developing gut of zebrafish. Knockdown of dscama, dscamb and bace2 caused a reduction of enteric neurons in hindgut of zebrafish. Over expression of DSCAM and bace2 had no effects on neuron number in the hindgut of zebrafish. Our results suggested that common variation of DSCAM contributed to HSCR risk in Han Chinese. The dysfunction of both dscams and bace2 caused defects in enteric neuron, indicating that DSCAM and BACE2 might play functional roles in the occurrence of HSCR. These novel findings might shed new light on the pathogenesis of HSCR.